COUNTERING RADICALISM THROUGH TAFSIR: State and Jihad in Indonesia’s Thematic Quranic Interpretation - Taufik, Ahmad; Anwar, Hamdani; Kusmana, Kusmana; Zakaria, Wan Fariza Alyati Wan; Kailani, Mohd (Ulul Albab: Jurnal Studi Islam, 2025)
Indonesia has witnessed a rise in radical ideologies that threaten unity, promote intolerance, and incite violence, as radicalism become more complex and adaptive. In response, the Ministry of Religious Affairs undertaken various counter-radicalization initiatives, notably through the Tafsir al-Quran Tematik publication. Among many themes addressed, the most notably ideas are jihad and statehood. This article explores the construction of counter-radical discourse by MoRA through this institutional tafsir, analyzing its function as a state instrument. Employing qualitative methods and Foucault’s power relations theory, the study integrates data from interviews with the tafsir’s authors, reader surveys, content analysis, and archival review. The findings reveal that Tafsir al-Quran Tematik defines jihad as a defensive act. It presents jihad as non-violent efforts like seeking knowledge and defending faith ethically. It emphasizes that jihad must follow moral guidelines rooted in the Prophet’s example. Additionally, the tafsir affirms that Islam does not mandate a specific government form, like caliphate, and supports the compatibility of the Indonesian state with Islamic principles. Drawing on Foucault’s theory, the state uses this tafsir to influence shaping religious discourse to legitimize national unity, promote moderate Islam, and delegitimize radical ideology. While promoting religious moderation, this state-endorsed tafsir centralizes interpretive authority under state auspices, potentially marginalizing individual Quranic interpreters. By positioning state-sponsored exegesis as the normative reference, the initiative risks undermining the pluralism and independence traditionally valued in Islamic scholarship. This study contributes to the discourse on state-religion dynamics, institutional authority, and the politics of religious interpretation in contemporary Indonesia.